2020
DOI: 10.1002/rcs.2067
|View full text |Cite
|
Sign up to set email alerts
|

Virtual, augmented, and mixed reality applications in orthopedic surgery

Abstract: Background Innovation in computer‐assisted surgery (CAS) aims to increase operative accuracy and improve safety by decreasing procedure‐related complications. The application of reality technologies, to CAS has begun to revolutionize orthopedic training and practice. Methods For this review, relevant published reports were found via searches of Medline (PubMed) data base using the following medical subject headings (MeSH) terms: “virtual reality” or “augmented reality” or “mixed reality” with “orthopedics” or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 58 publications
0
91
0
3
Order By: Relevance
“…The incorporation of an aiming beam to track the measurement location permits real‐time display of individual or combined FLIm parameters superimposed to an image of the surgical field‐of‐view for an augmented reality visualization experience [110, 118]. For applications where the current standard of care does not require an imaging system (ie, cameras), mixed‐reality visualization approaches with goggles or ancillary screens could enable enhanced surgical guidance [232–237].…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of an aiming beam to track the measurement location permits real‐time display of individual or combined FLIm parameters superimposed to an image of the surgical field‐of‐view for an augmented reality visualization experience [110, 118]. For applications where the current standard of care does not require an imaging system (ie, cameras), mixed‐reality visualization approaches with goggles or ancillary screens could enable enhanced surgical guidance [232–237].…”
Section: Discussionmentioning
confidence: 99%
“…Ved bruk av holografisk teknologi med blandet virkelighet (12) kan vi gjøre en leddundersøkelse der vi ser hvordan skjelettet beveger seg mens vi undersøker pasienten. CT-bilder av bekken og hofter brukes for å lage et hologram av bekkenet og hoftene.…”
Section: Ortopedisk Kirurgiunclassified
“…Mixed‐reality (MR) technology introduces virtual scenes to the real environment and establishes an interactive feedback information loop between the virtual world, the real world, and the user 6 . Verhey et al 7 introduced the concept that MR technology can be helpful for preoperative operation plan formulation by a 360 degree panoramic display of a renal tumor without a dead angle, which contributes to improving preoperative planning efficiency and has better familiarity with patient anatomy. Yoshida et al 8 reported that real‐time imaging of intraoperative MRASN can be conducive to the tracking and location of tumors and improve the accuracy of renal tumor resection.…”
Section: Introductionmentioning
confidence: 99%